Preserved Kondo effect of small cobalt atomic chains on Ru(0001) surface - Feng, Wei; Liu, Qin; Zhou, Chunsheng; Lai, Xinchun; Li, Bin; Zhao, Aidi (New journal of physics, 2016)
The evolution of the Kondo effect from a cobalt monomer to a compact dimer, a linear trimer and then a triangular trimer on Ru(0001) surface was studied by atomic manipulation and scanning tunneling spectroscopy (STS). It is found that the Kondo resonances of a compact Co dimer and linear trimer still can be detected in their STS because of the weak ferromagnetic exchange interaction between the Co atoms. However, when the number of the nearest-neighbors for every Co atom in the compact Co clusters is larger than one, for the interaction between Co atoms enter into the regime of the strong ferromagnetic exchange interaction, the Kondo resonance disappear and a new state forms.